Constituição das identidades docentes de egressas/os do curso de Pedagogia EAD como segunda graduação - Heinle, Vivian (Universidade do Vale do Rio dos Sinos, 2024)
This research investigates the educational trajectories of graduates of the distance learning Pedagogy course, who chose it as their second degree, in order to understand how their teaching identities are constituted, based on their narratives. To do this, we carried out a characterization questionnaire and an individual narrative interview on WhatsApp with 15 people — whether or not they work in the field of education — who studied at universities in Rio Grande do Sul, with hubs in various cities. From a post-structuralist perspective, based on Studies in Teaching and Studies in Pedagogy, the tool-concepts of identity and teaching were used to answer the research problem, which was explained by the following question: in what ways are the teaching identities of graduates of the distance learning Pedagogy course as a second degree constituted from the narratives of their educational trajectories? After analyzing the narratives of the research participants and identifying some points in common, such as the acceleration of time and the precariousness of the training process, the thesis defended is that the ways of being a teacher and practicing the profession are crossed and constituted by processes of acceleration and precariousness, forged by the macro-political contexts of teacher training in Brazil today, and by the training trajectories of the graduates of distance learning Pedagogy courses.
Keywords: Pedagogia; EAD; Segunda graduação; Identidade; Docência; Pedagogy; Distance learning; Second degree; Identity; Teaching; ACCNPQ::Ciências Humanas::Educação